Orodia as Living Ethics: Negotiating Meukisi Indigenous Spirituality and Christian Moral Values in Character Education - Simon Tabuni; Yuli Haolngap (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study examines Orodia as a living ethical system within the Meukisi indigenous community in Papua, Indonesia, and analyzes its integration with Christian moral values in the construction of character education. The research responds to the tendency to separate religion and custom, particularly in indigenous societies where spiritual beliefs, cultural traditions, and moral practices are deeply interconnected. Using a qualitative ethnographic approach, data were collected through in-depth interviews, participant observation, and document analysis involving traditional leaders, church leaders, elders, parents, youth representatives, and community members. The data were analyzed thematically within an interpretive sociological framework. The findings reveal that the seven principles of Orodia—akoi-akoi, betoi-betoi, dekoi-dekoi, kenabise, temeh, tevrei, and yau—function as moral mechanisms that regulate diligence, obedience, respect, love, peace, accountability, reconciliation, and communal fellowship. The study further demonstrates that Christianity does not replace indigenous spirituality, but reinforces and reinterprets the ethical meanings embedded in Orodia. This integration produces a contextual model of character education grounded in local wisdom, communal responsibility, and religious morality. The study contributes to indigenous education, sociology of religion, and character education by affirming Orodia as a culturally rooted framework for shaping ethical consciousness and social harmony.